Usaha Kader Penerima Beasiswa Unggulan Muhammadiyah Untuk Meningkatkan Prestasi Akademik (Studi Kasus Kader Universitas Muhammadiyah Surakarta 2014) - Hidayati, Solichah Nurul; , Dr. Abdullah Aly M.Ag (2017)
Academic achievement is a learning process experienced by students and produces changes in the field of knowledge, comprehension, application, power analysis, synthesis and evaluation. Achievement will never be produced without any effort on either knowledge or skills. Muhammadiyah Leading Cadres Scholarship represents the ideals of Muhammadiyah in the field of education with the aim of making excellent students and actively participate in student activities oriented in Muhammadiyah without neglecting the main task of a student that's academic activities. This study examines efforts of the grantee to improve the academic achivement: Case Study of cadre in Muhammadiyah University of Surakarta (UMS) 2014. The problems of research are formulated as (1) How is the academic achievement of the grantee? (2) What effort does the grantee cadres to improve their academic achievement? This is a field research with a qualitative approach meaning that this research requires the writer to enter directly into the field of study, then interact directly with data resources to obtain valid and accurate data as needed. This study tooks place in UMS to the subject of scholarship student class of 2014. Technique of collecting data use interviews, observation, and documentation. Meanwhile data analysis is conducted by the inductive method that covers reducing the data, data presentation, and drawing conclusions. The results of this study indicate that the Muhammadiyah grantee students in the UMS 2014 academic year as many as 45 students who are divided into several faculties have a good academic achievement in average. Factors affecting students' academic achievement among cadre grantee is motivation, family and the college. The efforts done by cadre grantee are study hard, be good at allocating time and the role of the UMS advisor.